Śaivism and the tantric traditions: essays in honour of Alexis G.J.S. Sanderson - Goodall, Dominic; Hatley, Shaman; Isaacson, Harunaga; Raman, Srilata; Sanderson, Alexis (Gonda indological studies, 2020)
Early Śaivism -- Exegetical and Philosophical Traditions -- Religion, the State, and Social History -- Mantra, Ritual, and Yoga -- Art and Architecture.